Provincial religious centers in the inka empire : propagators of official ideology or spaces for local resistance? - López-Hurtado, Enrique (Pontificia Universidad Católica del Perú. Fondo Editorial, 2010)
The incorporation of provincial religious centers into the Inka empire has been discussed basically from two different points of view. The first, proposed by Bauer and Stanish (2002), is based in their work on the Islands of the Sun and the Moon in Lake Titicaca. In this model, provincial religious centers were primarily propagators of state ideology, political platforms whose function was to legitimize Inka control and facilitate the administration of the region.

La incorporación de centros religiosos provinciales en el imperio incaico ha sido enfocada básicamente desde dos puntos de vista distintos. El primero es propuesto por Bauer y Stanish (2001) y está basado en su estudio de las islas del Sol y de la Luna en el Lago Titicaca. En este modelo los centros religiosos provinciales eran principalmente difusores de la ideología estatal y plataformas políticas cuya función era legitimar el control incaico para facilitar la administración de estas regiones.
Centros religiosos provinciales en el imperio incaico : ¿difusores de la ideología oficial o espacios de resistencia local?
Páginas 213-229
Keywords: Incas--Política y gobierno; Incas--Religión; Incas--Restos arqueológicos; https://purl.org/pe-repo/ocde/ford#6.01.02